Seasonal and interannual variability of sea-surface carbon dioxide species at the European Station for time series in the Ocean at the Canary Islands (ESTOC) between 1996 and 2000 - González-Dávila, Melchor; Santana-Casiano, J. Magdalena; Rueda, Maria José; Llinás, Octavio; González-Dávila, Enrique Francisco (0886-6236, 2003)
Seasonal patterns in hydrography, partial pressure of CO2, fCO2, pHt, total alkalinity, AT, total dissolved inorganic carbon, CT, nutrients, and chlorophyll a were measured in surface waters on monthly cruises at the European Station for Time Series in the Ocean at the Canary Islands (ESTOC) located in the northeast Atlantic subtropical gyre. With over 5 years of oceanographic data starting in 1996, seasonal and interannual trends of CO2 species and air‐sea exchange of CO2 were determined. Net CO2 fluxes show this area acts as a minor source of CO2, with an average outgassing value of 179 mmol CO2 m−2 yr−1 controlled by the dominant trade winds blowing from May to August. The effect of short‐term wind variability on the CO2 flux has been addressed by increasing air‐sea fluxes by 63% for 6‐hourly sampling frequency. The processes governing the monthly variations of CT have been determined. From March to October, when CT decreases, mixing at the base of the mixed layer (11.5 ± 1.5 mmol m−3) is compensated by air‐sea exchange, and a net organic production of 25.5 ± 5.7 mmol m−3 is estimated. On an annual scale, biological drawdown accounts for the decrease in inorganic carbon from March to October, while mixing processes control the CT increase from October to the end of autumn. After removing seasonality variability, fCO2sw increases at a rate of 0.71 ± 5.1 μatm yr−1, and as a response to the atmospheric trend, inorganic carbon increases at a rate of 0.39 ± 1.6 μmol kg−1 yr−1.